2018
DOI: 10.1126/scitranslmed.aam9507
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of endothelial dysfunction reduces white matter vulnerability in cerebral small vessel disease in rats

Abstract: One Sentence Summary: In cerebral small vessel disease, endothelial dysfunction leads to white matter vulnerability which is reversible in a rat model with endothelial stabilizing drugs.Abstract: Dementia is a major social and economic problem for our ageing population. One of the commonest causes of dementia in the elderly is cerebral small vessel disease (SVD).Magnetic resonance scans of SVD patients typically show white matter abnormalities, but we do not understand the mechanistic pathological link between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
156
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 78 publications
4
156
1
1
Order By: Relevance
“…42,43 The decreased expression of claudin-5, the key tight junction protein of the BBB, has been reported in a CSVD model. 38 In addition, growing evidence has indicated that limited caveolae-mediated transcytosis maintains BBB integrity in the CNS, 44 and BBB disruption due to increased vesicle transport has been confirmed in many models. 27,45 Cav-1 is a major structural component of caveolae and is mainly expressed in the vessels of the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…42,43 The decreased expression of claudin-5, the key tight junction protein of the BBB, has been reported in a CSVD model. 38 In addition, growing evidence has indicated that limited caveolae-mediated transcytosis maintains BBB integrity in the CNS, 44 and BBB disruption due to increased vesicle transport has been confirmed in many models. 27,45 Cav-1 is a major structural component of caveolae and is mainly expressed in the vessels of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of CSVD has also been evaluated in animal models. Rajani et al reported that mature oligodendrocytes are decreased, which implies abnormal myelination. In the CNS, MBP and NF200 are the critical components of myelin and axons, and their integrity plays an important role in maintaining the conduction of nerve fiber bundles .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Senescent cells accumulate in tissues and organs, where they play a detrimental role in the aging process (48)(49)(50)(51). Senescent ECs could contribute to cerebrovascular dysfunction by: 1) inhibiting EC replacement and regeneration in response to ageing and aberrant angiogenic signals; 2) inducing changes in tight junction protein expression and coverage (52), leading to blood-brain barrier alterations and leakiness; and 3) inducing local inflammatory responses and secreting proinflammatory cytokines (28) to cause further damage to the neurovascular unit or secrete other factors, such as HSP90a, which was recently shown to inhibit oligodendrocyte maturation in a rat model of cerebral small vessel disease (53). All of these pathogenic responses by dysfunctional ECs could cause further collateral damage to the neurovascular unit, ultimately leading to neurodegeneration and cognitive deficits in the AD brain.…”
Section: Discussionmentioning
confidence: 99%